Advances in metal–organic framework-based hydrogel materials: preparation, properties and applications. Issue 5 (12th January 2023) - Sun, Wang; Zhao, Xianhui; Webb, Erin; Xu, Gang; Zhang, Weijie; Wang, Yang
Abstract : This review provides the engineering strategies, systematic classification and representative applications of MOF-based hydrogels, and future prospects have also been presented in detail. Abstract : Although metal–organic frameworks (MOFs) with intriguing physiochemical properties have recently attracted increasing attention of researchers, MOFs have not adequately achieved various applications due to their instability and unsatisfactory processability. Hence, MOF-based composites as well as structurally novel MOFs have been established to solve this challenge. Recently, some efforts have been made for the development of MOF-based hydrogels. They exhibit excellent properties compared to initial MOFs in many ways ( e.g., mechanical strength, absorption capacity and total pore volume). In this review, the up-to-date research progress of MOF-based hydrogels will be briefly summarized. We mainly focus on expounding the classification of MOF-based hydrogels and their related synergistic effects. As to details, we will provide a conspectus of laconic and latest approaches for the synthesis of MOF-based hydrogels, focusing on composite systems, mechanism research, and stability. In addition, the applications of MOF-based hydrogels have been widely discussed, particularly in the environmental, energy and medical aspects. It is hoped that the detailed description of this review can help researchers working on MOF-based hydrogels to develop more novel composite materials and investigate their wider application.